Characterisation and function of TRIM23 in grass carp (Ctenopharyngodon idella). Issue 88 (May 2019) - Chu, Pengfei; He, Libo; Yang, Cheng; Li, Yangyu; Huang, Rong; Liao, Lanjie; Li, Yongming; Zhu, Zuoyan; Wang, Yaping
Abstract: Tripartite motif (TRIM) proteins are key components of the innate immune system, functioning as antiviral restriction factors or modulating signaling cascades that lead to proinflammatory cytokine induction. In the present study, the TRIM family gene TRIM23 from grass carp ( Ctenopharyngodon idella ) was cloned and characterised. TRIM23 was moderately expressed in the examined tissues, and the significantly altered expression was observed after grass carp reovirus (GCRV) and poly(I:C) infection. Dual-luciferase activity assay showed that TRIM23, especially its C-terminal domain ARF, depressed the promoter activity of IRF3 and IRF7 . The subcellular localisation showed that TRIM23 protein was located in the cytoplasm and could be recruited by both TRAF6 and MyD88. Furthermore, TRIM23 was confirmed to interact with either TRAF6 or MyD88 by the bimolecular fluorescence complementation (BiFC) system in CIK cells. Additionally, autophagy was enhanced by over-expressed TRIM23 in 293T cells. Taken together, our results demonstrate that TRIM23 gene plays an important role in innate immune regulation and provide new insights into understanding the functional characteristics of the TRIM23 in teleosts. Highlights: The TRIM23 gene in grass carp ( Ctenopharyngodon idella ) was identified and analysed. Expression and transcriptional regulation of TRIM23 gene were investigated. TRIM23 involved in the regulation of the promoter activity of IRF3 and IRF7. The TRIM23 protein could colocalise and interact with TRAF6 and MyD88 in CIK cells. The TRIM23 protein could induce autophagy.